Pengaruh Persepsi dan Pengetahuan Masyarakat Terhadap Minat Menjadi Nasabah Bank Syariah - Masruchin; Lestari, Novieati Dwi (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
The potential for the development of Islamic banks in Sidoarjo Regency is very large because there are 18 sub-districts with a majority of Muslim populations, one of which is Sukodono. However, the amount of potential is not in line with the growth of Islamic banking. This is due to the low perception of Muslims towards Islamic banking, which is due to the lack of knowledge about the Islamic banking system which ultimately has an impact on the low interest in becoming Islamic banking customers. The purpose of this study is to determine and test the influence of public perception and knowledge on interest in becoming Islamic bank customers. This study used quantitative methods by giving questionnaires to 103 people in Sukodono District. The results of the study were processed using SPSS software version 22 which showed that perception directly affects interest in becoming Islamic bank customers with significance value (0.00 < 0.05), public knowledge directly affects interest in becoming Islamic bank customers with significance value (0.00 < 0.05) and public perception and knowledge simultaneously affect interest in becoming Islamic bank customers with significance value (0.00 < 0.05). Thus, it can be interpreted that the influence of public perception and knowledge on interest in becoming Islamic bank customers is 69,9% while the remaining 31,1% is influenced by other variables.